Tort Liability of Medical Workers in the Patient Safety System in Ukraine and the World - Horislavska, Inna V.; Marits, Dariia O.; Piddubnyi, Oleksii Yu.; Shatkovska, Daryna M.; Shatkovskiy, Yaroslav M. (International Journal of Criminology and Sociology, 2022)
Health 2020: European health and well-being policy. It focuses on supporting the actions of governments and society in the direction of significantly improving the health and well-being of the population; reducing the level of inequality in receiving medical services; promoting the health of everyone; ensuring that the health care system is "human-centred". The position of the World Health Organization is unequivocal – "the most important general health issue internationally" is patient safety (an integral component of service quality). It was proven that the reduction in the number of medical errors and similar health-related situations is the result of the integration and coordination of services through the participation of patients and consumers of medical services. The purpose of the paper is to investigate and compare the features of tort liability of medical workers under the legislation of Ukraine and the standards of the World Health Organisation. Our research is based on such methods as comparative legal method, method of analysis, formal legal method, as well as bibliographic method. Semasiology of the concept of "tort liability" for health professionals in Ukraine has differences in comparison with the WHO standards. Accordingly, the level of patient safety in Ukraine is such that needs to be improved to meet international standards.